Berpikir Kritis Matematis Ditinjau dari Kemampuan Awal pada Topik Statistika - Risnawati, Risnawati; Hamdani, M. Fikri; Syarifuddin, Syarifuddin (MUST: Journal of Mathematics Education, Science and Technology, 2025)
This study aims to analyze students’ mathematical critical thinking skills in relation to their initial abilities on the topic of statistics. This investigation is essential because statistical topics require the ability to interpret data, analyze relationships between pieces of information, evaluate solution strategies, and draw inferences; therefore, initial ability plays a substantial role in shaping the quality of students’ critical thinking processes. The research employed a descriptive qualitative approach with an intrinsic case study design to explore in depth the characteristics of students’ critical thinking based on their initial ability categories. The participants consisted of six seventh-grade students selected according to their levels of initial ability low, medium, and high. Data were collected through tests and interviews. The findings reveal that (1) students with low initial ability were only able to perform interpretation, (2) students with medium initial ability could perform interpretation, analysis, and evaluation though not yet completely, and (3) students with high initial ability were able to demonstrate all four indicators of critical thinking comprehensively. These results highlight the importance of considering students’ initial ability when designing assessments and learning activities that demand higher-order thinking skills (HOTS).